A half-space projection method for solving generalized Nash equilibrium problems. (3rd July 2017) - Ye, Minglu
Abstract : The generalized Nash equilibrium problem (GNEP) is an n -person noncooperative game in which each player's strategy set depends on the rivals' strategy set. In this paper, we presented a half-space projection method for solving the quasi-variational inequality problem which is a formulation of the GNEP. The difference from the known projection methods is due to the next iterate point in this method is obtained by directly projecting a point onto a half-space. Thus, our next iterate point can be represented explicitly. The global convergence is proved under the minimal assumptions. Compared with the known methods, this method can reduce one projection of a vector onto the strategy set per iteration. Numerical results show that this method not only outperforms the known method but is also less dependent on the initial value than the known method.